PENGARUH PROMOSI PENJUALAN DAN PERIKLANAN TERHADAP KEPUTUSAN PEMBELIAN PADA TABUNGAN SIMPEDES, PT BANK RAKYAT INDONESIA - Sri Wahyuni; Nessia Timmy; Artanty Artanty (STIE AUB Surakarta, 2016)
The banking industry has an important role in the economy that raise and distribute funds for community economic development. The more people who know and entrust their savings in banks. The banking industry has undergone major developments in recent years, state banks and private banks, giving rise to competition. This is because as the public awareness of the importance of the bank's presence in helping to meet the needs, including saving. This study with a total sample of 105 respondents. Data analysis was performed using Structural Equation Modeling (SEM) software application Amos 20.0 to test the causality of the two hypotheses of the study. The results showed that a significant difference between sales promotion and advertising on purchasing decisions, with the result variable is greater than the sales promotion advertisingvariables. Keywords: sales promotion, advertising, purchasing decisions, Structural Equation Modeling.